Pengaruh Musyawarah Guru Mata Pelajaran (MGMP) terhadap Profesionalitas Guru - Imelda Imelda; Adripen Adripen; Lita Sari Muchlis; Annisaul Khairat (ISLAMIKA, 2023)
There are many factors that can influence teacher professionalism, one of which is subject teacher deliberations. Therefore, this study aims to influence subject teacher deliberations on social studies teacher professionalism in MTsN throughout Tanah Datar District. This research uses a type of quantitative research with the Ex-Post Facto method. Data collection technique with a questionnaire. The population is social studies teachers at MTsN throughout Tanah Datar regency. The research sample was taken using random sampling by means of a lottery system. Data analysis using linear regression. The results showed that subject teacher deliberations had an effect on the professionalism of IPS teachers at MTsN Tanah Datar Regency by 57.4%. So it can be concluded that subject teacher deliberations affect teacher professionalism.